Comparative "Omics" of the Fusarium fujikuroi Species Complex Highlights Differences in Genetic Potential and Metabolite Synthesis - Niehaus, Eva-Maria; Münsterkötter, Martin; Proctor, Robert H; Brown, Daren W; Sharon, Amir; Idan, Yifat; Oren-Young, Liat; Sieber, Christian M; Novák, Ondřej; Pěnčík, Aleš; Tarkowská, Danuše; Hromadová, Kristýna; et al. (Genome biology and evolution, 2016)
Species of the Fusarium fujikuroi species complex (FFC) cause a wide spectrum of often devastating diseases on diverse agricultural crops, including coffee, fig, mango, maize, rice, and sugarcane. Although species within the FFC are difficult to distinguish by morphology, and their genes often share 90% sequence similarity, they can differ in host plant specificity and life style. FFC species can also produce structurally diverse secondary metabolites (SMs), including the mycotoxins fumonisins, fusarins, fusaric acid, and beauvericin, and the phytohormones gibberellins, auxins, and cytokinins. The spectrum of SMs produced can differ among closely related species, suggesting that SMs might be determinants of host specificity. To date, genomes of only a limited number of FFC species have been sequenced. Here, we provide draft genome sequences of three more members of the FFC: a single isolate of F. mangiferae, the cause of mango malformation, and two isolates of F. proliferatum, one a pathogen of maize and the other an orchid endophyte. We compared these genomes to publicly available genome sequences of three other FFC species. The comparisons revealed species-specific and isolate-specific differences in the composition and expression (in vitro and in planta) of genes involved in SM production including those for phytohormome biosynthesis. Such differences have the potential to impact host specificity and, as in the case of F. proliferatum, the pathogenic versus endophytic life style.
Keywords: Host Specificity; Zea mays; molekulární evoluce; Metabolome; fungální proteiny; polymorfismus genetický; Evolution, Molecular; kukuřice setá; Polymorphism, Genetic; metabolom; hostitelská specificita; Fusarium fujikuroi species complex; genome sequencing; metabolomics; Genome, Fungal; in planta expression; secondary metabolism; genom fungální; Mangifera; Orchidaceae; evolution; Fusarium; Fungal Proteins